2019
DOI: 10.1080/1828051x.2019.1659106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar sources and doses on fermentation dynamics, carbohydrates changes, in vitro digestibility and gas production of rice straw silage

Abstract: To elucidate the differences of various sugar sources and doses on rice straw silage, the effect of molasses (M, direct substrate) and fibrolytic enzyme (E, indirect substrate) with four doses on fermentation dynamics, carbohydrates and in vitro digestibility was evaluated. Molasses (0, 2, 3 and 4% of fresh weight) or fibrolytic enzyme (0, 0.02, 0.04 and 0.06%) were applied to fresh rice straw ensiling for 3, 6, 9, 15, 30 and 60 days. All additives increased lactic acid content and lactic/acetic acid, reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Similar fermentation patterns were observed between M I C I and M II C I silages, as well as between M I C II and M II C II silages, which might be interpreted that even if M I contained insufficient LAB (<10 5 cfu/g FW), the chemical quality of material (mainly WSC content) still determined the natural fermentation. Our previous study (Zhao et al, 2019) also found that sugar supplementation improved the fermentation quality of rice straw lacking LAB. Meanwhile, under the same epiphytic microbiota (M I or M II ) inoculation, changes of chemical composition had marked effects on the fermentation parameters of P. giganteum silage (M I C I vs. M I C II or M II C I vs. M II C II ).…”
Section: Effects Of Chemical and Microbial Factors On Fermentation Qu...mentioning
confidence: 77%
“…Similar fermentation patterns were observed between M I C I and M II C I silages, as well as between M I C II and M II C II silages, which might be interpreted that even if M I contained insufficient LAB (<10 5 cfu/g FW), the chemical quality of material (mainly WSC content) still determined the natural fermentation. Our previous study (Zhao et al, 2019) also found that sugar supplementation improved the fermentation quality of rice straw lacking LAB. Meanwhile, under the same epiphytic microbiota (M I or M II ) inoculation, changes of chemical composition had marked effects on the fermentation parameters of P. giganteum silage (M I C I vs. M I C II or M II C I vs. M II C II ).…”
Section: Effects Of Chemical and Microbial Factors On Fermentation Qu...mentioning
confidence: 77%
“…Zhao et al. (2019) reported a slow transition of homofermentation to heterofermentation which he solved by addition of molasses. In the current study, the fermentation in spontaneous process was originally dominated by the homofermenter ( L. lactis ) before the obligate heterofermenter ( L. brevis and genus Leuconostoc ) dominated the intermediate stage.…”
Section: Discussionmentioning
confidence: 99%
“…After harvesting, the rice straw commonly is preserved by making silage or hay. However, it has poor content of soluble carbohydrate after separating from its grains, which results in a low fermentation quality when it is preserved as silage [ 8 ]. The LAB cannot grow optimally with low content of soluble carbohydrate leading an inability to drop the pH rapidly during ensiling [ 9 ].…”
Section: Introductionmentioning
confidence: 99%